2011
DOI: 10.1007/s00421-011-2055-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of break-points in breathing pattern at the gas-exchange thresholds during incremental cycling in young, healthy subjects

Abstract: The present study investigated whether 'break-points' in breathing pattern correspond to the first ([Formula: see text]) and second gas-exchange thresholds ([Formula: see text]) during incremental cycling. We used polynomial spline smoothing to detect accelerations and decelerations in pulmonary gas-exchange data, which provided an objective means of 'break-point' detection without assumption of the number and shape of said 'break-points'. Twenty-eight recreational cyclists completed the study, with five indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 46 publications
(77 reference statements)
1
14
0
Order By: Relevance
“…When these devices have been used during exercise, f R is typically used for limited applications such as the estimation of the ventilatory threshold during incremental exercise (Hailstone and Kilding, 2011 ). Whilst, the disproportionate and progressive increase in f R , which begins with attainment of the first ventilatory threshold, may be used as a practical non-invasive method for estimating the ventilatory thresholds (Cross et al, 2012 ), there are other important reasons why athletes should consider monitoring f R during training.…”
Section: Current Applications Of Respiratory Wearablesmentioning
confidence: 99%
“…When these devices have been used during exercise, f R is typically used for limited applications such as the estimation of the ventilatory threshold during incremental exercise (Hailstone and Kilding, 2011 ). Whilst, the disproportionate and progressive increase in f R , which begins with attainment of the first ventilatory threshold, may be used as a practical non-invasive method for estimating the ventilatory thresholds (Cross et al, 2012 ), there are other important reasons why athletes should consider monitoring f R during training.…”
Section: Current Applications Of Respiratory Wearablesmentioning
confidence: 99%
“…For these reasons, studies based on electrocardiogram (ECG) derived parameters such as ventricular repolarization instability [7] or heart rate (HR) [1,8] were developed by researchers as cheap, simple to perform and non-invasive methods for determining ventilatory thresholds. A computerised method that used polynomial spline smoothing presented in [9] has been employed to determine these abrupt accelerations in respiratory rate which are considered surrogates of VT1 and VT2. The objective of this work is to propose a new method that estimates VT using the respiratory rate derived from single lead ECG.…”
Section: Introductionmentioning
confidence: 99%
“…From a practical standpoint, the EDR seems to yield equivalent RF patterns as the GE noted in Figure 3 . Since previous studies showed potential for RF breakpoints to correspond with ventilatory thresholds [ 2 ], it would be of interest to see if EDR could achieve a similar result. A recent publication showed that both first and second ventilatory threshold identification is possible with EDR methodology [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are scenarios in which RF estimation can be helpful in exercise science. These include ventilatory threshold measurements, assessments of work rate intensity, and decreases in exercise performance [ 2 , 3 , 4 ]. Though minute ventilation (the tidal volume x RF) has received attention for intensity estimation purposes [ 5 ], the respiratory rate itself has been shown to be quite sensitive in this regard as well [ 1 ].…”
Section: Introductionmentioning
confidence: 99%